(untitled) (LACCEI, 2024)
In this article we address the issue of database management for the control of a thermoelectric power generator through a river water treatment process. The management process has been carried out using the Microsoft ACCESS database platform. In this research work, database management is similar to a SCADA system, which is generally used for the management, supervision, auditing and control of a network of industrial processes. In a similar way, our database management system has been used to carry out the simulation to audit and control process variables such as: voltage, current, level of stored water, level of treated water for consumption, steam pressure, level of temperature, levels of electrical consumption, as well as the results of the management of the work of the technical and administrative personnel, among others. In this work we show another alternative for the management, supervision, auditing and control of an electric power generator and at the same time for river water treatment for domestic use, given the scarce energy resources and limited supplies of treated water.